2009
DOI: 10.1080/02772240802175814
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of antimony (Sb) in piglets orally given graded levels of Sb (V)

Abstract: International audienceThe potential risks from oral intake of soil antimony (Sb) depends mainly on the amount of metal ingested and its bioavailability. Relative bioavailability may be determined by comparing Sb present in soil to a reference compound, taking into account accumulation in different target tissues or excretion. However, due to the lack of scientific knowledge concerning the fate of Sb in the organism, there is a need to study the absorption and distribution of Sb in order to select target tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The initial step of the RBA assessment was to assess the dose–response for Sb accumulation in the target tissue or organs in order to select a suitable endpoint for RBA assessment. Previous studies showed that the Sb distribution in mammals varied when different Sb species, such as Sb (V in potassium antimonate and Sb (III) in potassium tartrate (C 4 H 4 KO 7 Sb, APT), were utilized. , Our preliminary tests showed that Sb (III) was the main species in beverages following incubation at 60 °C for 7 days (Figure S1, the detailed process for Sb speciation can be found in Supporting Information), so APT was chosen as the reference compound to investigate Sb RBA. In addition, for the assessment of RBA, the properties of the reference material need to be similar to that of the samples to be assessed.…”
Section: Methodsmentioning
confidence: 99%
“…The initial step of the RBA assessment was to assess the dose–response for Sb accumulation in the target tissue or organs in order to select a suitable endpoint for RBA assessment. Previous studies showed that the Sb distribution in mammals varied when different Sb species, such as Sb (V in potassium antimonate and Sb (III) in potassium tartrate (C 4 H 4 KO 7 Sb, APT), were utilized. , Our preliminary tests showed that Sb (III) was the main species in beverages following incubation at 60 °C for 7 days (Figure S1, the detailed process for Sb speciation can be found in Supporting Information), so APT was chosen as the reference compound to investigate Sb RBA. In addition, for the assessment of RBA, the properties of the reference material need to be similar to that of the samples to be assessed.…”
Section: Methodsmentioning
confidence: 99%